Impact of culture on autobiographical life structure in depression - Jobson, Laura; Miskon, Nazleen; Dalgleish, Tim; Hitchcock, Caitlin; Hill, Emma; Golden, Ann Marie; Zulkefly, Nor Sheereen; Mukhtar, Firdaus (Wiley, 2018)
Objectives: Distortions in autobiographical memory have been implicated in major depressive disorder (MDD). Those with MDD demonstrate a ‘depressogenic’ autobiographical life structure. Research has not examined how culture influences this process. We investigated whether Malay individuals (members of an interdependent culture) with MDD demonstrated a ‘depressogenic’ autobiographical life structure similar to that of British individuals (members of an independent culture) with MDD. Design: A 2 (Culture; Malay, British) × 2 (Mood; depressed, control) cross‐sectional design using a card sort task and self‐report measures was used. Methods: Malay individuals with MDD or no history of MDD completed the life‐structure card‐sorting task, which provided a novel method for investigating organizational structure of the life narrative. These data were compared to previously collected data in which British individuals with MDD or without MDD had completed the same task within the same experimental protocol. Results: Pan‐culturally those with MDD had greater negativity (i.e., used more negative attributes), negative redundancy (i.e., used the same negative attributes repeatedly across life chapters) and negative emodiversity (i.e., had greater variety and relative abundance of negative attributes), and reduced positive redundancy (i.e., used the same positive attributes repeatedly across chapters) in their structuring relative to controls. While the British MDD group had greater compartmentalization (i.e., the negative and positive attributes were clustered separately across different chapters) than British controls, the Malay MDD group had lower levels of compartmentalization than Malay controls. Conclusions: The findings suggest culture may shape aspects of the autobiographical life structure in MDD.